A systematic approach to mastering green competencies: European Green Deal - Hrinchenko, H.; Mykolaiko, V.; Kovtun, O. (Problems of Engineer-Pedagogical Education, 2023)
The article is devoted to the development of a systematic approach to the development of green competences in higher education institutions. The systematic approach proposed in the article is based on the European Sustainable Development Competence Framework (GreenComp), which was developed by the European Commission to support the European Green Deal. The GreenComp is a universal model that aims to foster sustainable thinking, environmental awareness and responsibility, based on a consensus understanding of what constitutes sustainable development as a competence. The paper analyses the competences that make up GreenComp, which are grouped into four areas and are the basis for improving educational programmes of any kind. Since GreenComp is intended for all students, regardless of their age and level of education, as well as for any learning environment – formal, non-formal and informal, the article proposes to integrate the GreenComp into the educational and research activities of higher education students of all levels. Separate educational components on sustainable development are proposed at the following educational levels: junior bachelor, bachelor and master degrees, as well as at the third educational and scientific level, which is PhD. To ensure the effectiveness and consistency of the acquired knowledge and skills, it is proposed to introduce elements of sustainable development education in general and specialised (vocational) educational components within formal education. Each of the proposed educational components combines the general goals of acquiring green competences and is improved with each level of education, which makes it possible to master, consolidate and improve the acquired competences at each level. In addition to the educational components that ensure the study of green competences, it is proposed to introduce elements of GreenComp learning into all educational components. As part of a systemic approach, the article proposes non-formal and informal education measures that allow fostering sustainable thinking in everyday life and activities and develop responsibility and potential of higher education students in the field of sustainable development.